The Law as a Drawbar, or Judicial Arbitrariness: Recidivism = Repetition of Crimes in the Framework of Circumstances Aggravating the Punishment - Ya. H. Lyzohub (Law and Safety)
The author has studied the current problem in Ukrainian criminal law – the problem of the courts’ understanding of the general jurisdiction of the repetition of offences, as well as their recidivism in the framework of the circumstances aggravating criminal punishment. Attention at the beginning of the paper, has been paid to the importance of understanding the regulatory act as the main source of criminal law in Ukraine. It has been demonstrated that it is the regulatory act that should determine the rules, which should be obeyed by the judicial authorities of Ukraine. It has been emphasized that it is necessary to take into account the law while interpreting the prescriptions of normative acts by the national courts; it has been stressed that such interpretation should proceed from the definitions and formulations available, first of all, in the legislation. The author has emphasized on the importance of adhering to the rules and regulations, in the course of such interpretation, used in the law without such unreasonable extension or distortion of their content by relevant court decisions.